Chapter La documentazione archivistica fra tardo Medioevo ed età moderna - Vestri, Veronica (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The essay, starting from a survey of the tradition of documentary sources related to San Miniato, focuses on the archival papers concerning the abbey in the late Medieval and Modern period, trying to indicate some historical-archival research paths. It is pointed out that much of the documentation is now dispersed or can only be consulted through erudite transcriptions, and possible forms of collating texts are outlined. At the end there is a memorial of 1533 which offers an insight into the conditions of the religious community and the damage the abbey suffered during the siege of Florence period.